Gerungisme, “Kitab Suci Fiksi”: Logical and Epistemological Analysis - Zainal Pikri (AIUA Journal of Islamic Education, 2019)
The statement of Rocky Gerung (RG), a popular thinker in Indonesia, that "If I use the definition that fiction activates imagination, the holy book is fiction" at the Indonesia Lawyers Club (ILC), Tuesday (04/10/2018) has caused controversy both in lay circles and philosophy lecturers in Indonesia. Even reported to the Police of the Republic of Indonesia as a statement that blasphemed religion. To be fair in this matter, this paper uses Husserl's phenomenological approach by putting in epoché all beliefs about the scriptures, especially those adopted by the author, to understand the "Holy Book is Fiction" in the conception of Rocky Gerung (RG). This approach allows the author to understand the concept of RG without being disturbed by initial perceptions, religious beliefs and the author's point of view. Then, the author moves to put the concept of RG in the discussion of contemporary logic that develops in analytic philosophy, namely modal logic, to analyze the possibility of the truth that "Holy Book is Fiction." Furthermore, the author identifies an epistemological position that enables one to view eschatological knowledge in the scriptures as something fictional not real and factual. It is hoped that this paper will unravel the confusion surrounding this controversy.